Environmental movements, state and civil society - Naik, Iswar Chandra (Jaipur : Rawat Publications, 2016)
Study with reference to Kashipur in Rayagada District of Odisha.
Includes bibliographical references (245-259) and index.
Keywords: Environmentalism -- India -- Kashipur; Industrialization -- Environmental aspects -- India -- Kashipur; Environmental policy -- India -- Kashipur; Kashipur (India) -- Politics and government